Análisis multitemporal y dinámícas fluviales del brazo de Mompox (río Magdalena), corregimiento de Cantera, Bolívar, Colombia - Castro Padilla, Ricardo Antonio; Jiménez Peñaranda, Camilo Eduardo; Rojas Martínez, Elías Ernesto; Lascarro Navarro, Frank David; Manco, Dino Carmelo (Ingeniería, 2022)
Context: The Mompox branch (Magdalena River), is located in an area characterized by low elevations, and its fluvial dynamics tends to overflow its channel and flood surrounding areas in periods of heavy rains. The objective of this research is to determine the fluvial dynamics of the Mompox branch, in the township of Cantera, Bolivar, Colombia, through the multitemporal analysis of satellite images. Method: A bibliographic review was carried out, as well as an analysis of the average, minimum, and maximum flow in the hydrometeorological stations of IDEAM (Institute of Hydrology, Meteorology, and Environmental Studies) located in the surroundings of the analyzed area; Subsequently, a geomorphology was captured using satellite images from 1960, 1969, and 1977 (for wet periods), and 2009, 2014, and 2017 (for dry periods). Results: The sub-basin of the Mompox branch has a flat smoothed topography; the elevations vary approximately one meter from one to the other. It has a meandering fluvial system with braided stationary drains, parallel to the Mompox branch. The drains and channels are interconnected with depressions (swamps and wetlands) that store bodies of water for a considerable time throughout the year. These areas are known as flood plains. Conclusions: The Mompox branch shows an increase in its sinuosity, which by the natural erosive and depositional processes of the river. Its evolution is stable; it behaves like an anastomosed river, with meandering lines in some sectors. It plays an important role in floods and provides volumes of water in rainy periods, thus initiating the flooding process.